Automatic Dehydration Level Detection Devices - Diana Dwi Damayanti; Her Gumiwang Ariswati; I Dewa Gede Wisana; Hendra Winarno (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2020)
Dehydration is a condition that occurs when the loss of body fluids exceeds the amount entered in the body so that it can disrupt the balance of minerals in body fluids. Most people do not feel thirsty until finally, they experience a period of severe dehydration, which can cause physical, cognitive, fatigue; if not corrected immediately can cause death. The purpose of this study is to design a dehydration and urine pH detection devices automatically. The contribution of this study is that this device is equipped with urine pH measurement and automatic body fluid calculation. This device is able to detect urine color levels, read urine pH values ​​, and provide information on body fluids needed to treat the patient's condition when detected. The sensors used in this device are color sensor TCS34725, pH meter sensor module SKU-016 and DS18B20 temperature sensor, the calculation of the amount of fluid that must be entered automatically from the patient's body weight input. The programming uses Arduino Nano as the main controller with a 128x64 graphic LCD. From the testing that has been done, it is known that the percentage error in the module is 3.5%, which means that it is still in the tolerance value because the tolerance limit is 5%, for the sensitivity test results get a value of 60% and specificity of 70%. Thus, it shows that the device is feasible and can be implemented as a dehydration detection device that is carried out independently at home.